A STUDY ON THE FIFTH SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM IN WRITING EXPOSITION TEXT: THE ABILITY AND THE PROBLEMS - Susan Ira Nova; Corry Paskarina Antang; Natalina Asi; Rio Ranuwelum Maleh (IKIP Siliwangi, 2023)
Mastering writing skill for undergraduate students of English Education become a challenge. They must have the writing skill due to in the future they will be English teachers who will be teaching the skill to the students. This research was intended to find out the mastery level of writing exposition text and its majority problems. It used descriptive quantitative method to analyse the data. The result of this research was the mastery level of the respondents’ writing of exposition text was in range of beginning to developing level. The problems in writing were divided into two categories, internal problems and external problems. The internal majority problems were lack knowledge of exposition text; lack practice of writing; grammatical problems. The external problems were difficulty in understanding the explanation from the lecturer; too many kinds of text to be learnt; and lack of practice at class due to limitation of time. Keywords: Exposition Text; Problems in Writing; Writing Mastery Level